Critical review attacks and countermeasures in internet of things enabled environments - Kumar Ch, Mohan; Kameswara Rao, M (International Journal of Engineering and Technology, 2018)
Internet of Things (IoT) generally referred as Industry 4.0, Now a day’s Application Areas are everywhere like Smart Transportation, Smart Construction, Fitness monitoring, Energy Supervision, Construction managing, Environmental Supervise, Groceries supply chain. IoT has a compound network of smart nodes; information sending and receiving of nodes are through the Internet. In this process, it is vulnerable to attacks. In This paper, we review the possible attacks with respect to Cisco- Seven Layer model.
Keywords: IoT; thing; Security Attack; Industry 4.0; Countermeasures; lightweight protocols.